fo027266: NCOS project 1852 Organizing, training and education for the development of peasants in Mindanao, Filipijnen - 11.11.11
"Collection: Projectnummer: 1852; Zwart-witfoto, van sprekers die training geven in San Francisco, Agusan sur aan abaca-boeren APA-As. NCOS project 1852 Organizing, training and education for the development of peasants in Mindanao, Filipijnen 1986-1996. Een realisatie van KMP. Land/Regio: Filipijnen; Code: FILIPIJNEN/87; Projectnaam: Organizing, training and education for the development of peasants in Mindanao; Series: Projectnummer: 1852; Land/Regio: Filipijnen; Code: FILIPIJNEN/87; Projectnaam: Organizing, training and education for the development of peasants in Mindanao; FULL TEXT AVAILABLE AT AMSAB-ISH"